KEGIATAN CYBERBRANDING FEMALE DAILY NETWORK SEBAGAI ONE STOP BEAUTY DESTINATION - Annisa Aulia Yusuf; Setianti, Yanti; FX. Ari Agung Prastowo (Universitas Swadaya Gunung Jati, 2024)
Female Daily is a beauty media that started from a community in Indonesia that uses internet technology to carry out branding activities, which is now known as the Female Daily Network. This research aims to discover the cyberbanking process carried out by the Female Daily Network on the website to find out how FD provides information, interacts, and makes a difference from other similar competitors. This study uses a descriptive method, a positive paradigm with qualitative data types. The concept used in this study is Cyberbranding from Deirdre Breakenridge. Data collection techniques used in this study were interviews, observation, and documentation studies. This research shows that research on how the Female Daily Network carries out cyber-branding activities to make it a Stop Beauty Destination uses the social commerce site www.femaledaily.com. First, how to convey information is done. Second, the interaction part that takes place. Finally, how does Female Daily Network differentiate itself from other similar competitors? This research concludes that the Female Daily Network has not been able to achieve its goal of becoming a Stop Beauty Destination even though several stages have been carried out because there is a final stage that still needs to be improved, such as providing information about this feature, this goal cannot be fulfilled, and there is no difference in FD. which is very significant among online competitors.